2010
DOI: 10.1007/s10461-010-9693-0
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity and Sexual Risk in an HIV Endemic Community in Uganda

Abstract: Food insecurity has been linked to high-risk sexual behavior in sub-Saharan Africa, but there are limited data on these links among people living with HIV/AIDS, and on the mechanisms for how food insecurity predisposes individuals to risky sexual practices. We undertook a series of in-depth open-ended interviews with 41 individuals living with HIV/AIDS to understand the impact of food insecurity on sexual-risk behaviors. Participants were recruited from the Immune Suppression Clinic at the Mbarara University o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
138
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(153 citation statements)
references
References 29 publications
(32 reference statements)
13
138
1
1
Order By: Relevance
“…This effect was strongest among food insufficient females who had five times greater odds of inconsistent condom use when compared with food sufficient females. This effect maintained in a multivariable model that controlled for other economic and sociodemographic factors, and is consistent with ethnographic data linking food insecurity with inconsistent condom use (e.g., Miller et al, 2010).…”
Section: Food Insecurity and Hiv/aidssupporting
confidence: 83%
See 2 more Smart Citations
“…This effect was strongest among food insufficient females who had five times greater odds of inconsistent condom use when compared with food sufficient females. This effect maintained in a multivariable model that controlled for other economic and sociodemographic factors, and is consistent with ethnographic data linking food insecurity with inconsistent condom use (e.g., Miller et al, 2010).…”
Section: Food Insecurity and Hiv/aidssupporting
confidence: 83%
“…A high prevalence of food insecurity (nearly 50%) has also been documented among PLWHA in San Francisco, CA and Vancouver B.C., Canada (Normen et al, 2005;Weiser et al, 2009b). On the other side of the causal model, at least theoretically, household food insecurity can increase an individual's risk of acquiring HIV by constraining options and thus promoting behavioral changes that increase risk of sexually transmitted infections (Weiser et al, 2007), the rapidity with which HIV converts to AIDS (Weiser et al, 2009b), and uptake and adherence to ART (Miller et al, 2010;Weiser et al, 2010). There is now research into each of these links (reviewed in Anema et al, 2009).…”
Section: Food Insecurity and Hiv/aidsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study based on the data from Demographic Health Survey (DHS, 2006) in India concluded that TB control strategies should be targeted to the poorest populations that are most at risk, and should address the most important determinants of disease such as malnutrition and living conditions [68]. In addition, since the problems are fundamentally interdisciplinary in nature, solutions should therefore come from joint collaboration among mass media, sociologists, anthropologists and epidemiologists.…”
Section: Framework For Actionmentioning
confidence: 99%
“…Studies have shown that income is the most important determinant of inequity, and income also explains food insecurity because it limits one's ability to acquire healthy and safe foods [26][27][28] . Nonetheless, other sociodemographic determinants must be investigated, such as household size, education level, race, and basic sanitation, among others 29 .…”
Section: Discussionmentioning
confidence: 99%